Pengetahuan Remaja Putri Tentang Anemia - Prayogi, Agus Sarwo; Salsabila, Farah; Mendri, Ni Ketut; Prabowo, Tri; Aryad, Rokhib (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2023)
Background: Adolescence between the ages of 10 and 19 is a vulnerable period, at which age there are very rapid physical and mental changes (Adolescence Growth Spurt) so that adolescents need more nutrition. However, at this time of the millennium, teenage daughters are overly attentive to the image of their bodies, such as dieting or reducing food from animals, which are rich in iron. One factor in the problem is the low level of knowledge. It causes anemia that can occur because the iron consumed is not satisfied in the body. The aim is to find out the knowledge of anemia in teenage daughters. Methods: Quantitative descriptive research method with survey research design. Study population of teenage daughters of class X in high school N 1 Sedayu Bantul. The instruments in this research use a closed questionnaire. Proportionate Stratified Random Sampling, 68 respondents. Results: Obtained from 68 adolescent daughter respondents on an overview of knowledge about anemia with criteria of good knowledge. Conclusion: Knowledge of anemia is becoming so important for teenage daughters. Because by having knowledge of anemia, so he prevents anemia from occurring in himself in particular and in teenage daughters in general.